2014
DOI: 10.1093/scan/nsu006
|View full text |Cite
|
Sign up to set email alerts
|

Increased involvement of the parahippocampal gyri in a sad mood predicts future depressive symptoms

Abstract: Behavioral studies suggest a relationship between autobiographical memory, rumination and depression. The objective of this study was to determine whether remitted depressed patients show alterations in connectivity of the posterior cingulate cortex (PCC, a node in the default mode network) with the parahippocampal gyri (PHG, a region associated with autobiographical memory) while intensively recalling negative memories and whether this is related to daily life symptoms and to the further course of depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 54 publications
10
76
0
Order By: Relevance
“…Supporting this notion is our finding that stronger PCC connectivity during emotional processing was significantly associated with an earlier age of depression onset (Figure S2C). Connectivity between the PCC and parahippocampal cortex during recollection of negative life events has also been shown to increase with the number of depressive episodes, as well as the frequency and subsequent prediction of sad mood in daily life (128). Individuals with an increased genetic risk for developing depression also exhibit altered PCC connectivity with the amygdala during emotional regulation—but not during resting-state (129).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion is our finding that stronger PCC connectivity during emotional processing was significantly associated with an earlier age of depression onset (Figure S2C). Connectivity between the PCC and parahippocampal cortex during recollection of negative life events has also been shown to increase with the number of depressive episodes, as well as the frequency and subsequent prediction of sad mood in daily life (128). Individuals with an increased genetic risk for developing depression also exhibit altered PCC connectivity with the amygdala during emotional regulation—but not during resting-state (129).…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has recently shown that individuals with a high risk of mood disorders who are homozygous for risk haplotype of the DGKH gene show relatively greater brain activation of the right parahippocampus during a verbal fluency task as compared with low-risk haplotype subjects, with the reverse pattern being observed for healthy control subjects (53). Furthermore, it has been shown that remitted depressed patients maintain an increased connectivity of the posterior cingulate cortex with the parahippocampal gyrus and that greater connectivity appears to represent a prognostic factor for future depressive episodes (54).…”
Section: Discussionmentioning
confidence: 99%
“…The medial temporal lobe in general, and more particularly the parahippocampal gyrus, has also been postulated to mediate self-referential associations in depression (Bar, 2009). Increased connectivity between this region and the posterior cingulate cortex could mediate the relationship between autobiographical memories and rumination and represent a neural substrate of vulnerability to depressive episodes (Zamoscik, Huffziger, Ebner-Priemer, Kuehner, & Kirsch, 2014). A link between rumination tendency and hippocampus activation has also recently been suggested (Mandell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%